THE EFFECT OF WORK CHARACTERISTICS, WORK ENVIRONMENT AND WORK MOTIVATION THE ORGANIZATION COMMITTEE OF EMPLOYEES SECRETARIATS OF BIMA REGENCY - Ahyani Ahyani (Lembaga Penelitian dan Pendidikan Mandala, 2020)
This research was motivated by employee commitment The Regional Secretariat of Bima Regency is classified as low. Employee commitment can be seen from the level of discipline or compliance in the form of loyalty to the task assigned to it. Then lazy employees are important evidence of low loyalty to tasks and responsibilities in advancing the organization. commitment to the organization will be seen to what extent an individual works with high enthusiasm and a strong willingness to remain in an organization to fight for the organization's vision, mission, values and goals.Many factors affect employee performance including job characteristics, work environment and work motivation.The purpose of this study was to determine and analyze the Effect of Job Characteristics, Work Environment and Work Motivation Against the Commitment of Organizations of the Bima Regency Secretariat Employees. This research was conducted with a quantitative method with an associative approach.The population of this research is the entire ASN within the scope of the Bima Regency Secretariat. The study population was determined by either 175 employees or had never been promoted.Data analysis methods used are descriptive analysis, regression requirements test, multiple regression analysis and also hypothesis testing.After calculating it is known that a significant level of 0.00 <0.05 and F arithmetic = 10,170> F table = 6,912 means that the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) reads